PENGEMBANGAN LKS BERBASIS PREDICT OBSERVE EXPLANATION PADA SUBMATERI KEANEKARAGAMAN HAYATI KELAS X - Rafikayuni, Rafikayuni; Aryati, Eka; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed to know validity of student worksheet base on POE of biodiversity sub-material of the tenth grade of senior high school. The method that was used in this research was a development research consisted of 2 phase preliminary and formative evaluation. Techniques of data collection of this research was marking sheet. As the research result, student worksheet base on POE that was develop validation were a lecturer and teacher. According to the assessment that was given by the validators, student worksheet base on POE belongs to the very high validity category with value of Vc=1,00 for all criteria including content utility with value of Vc=1,00 very high validity category, language worthiness with value of Vc=1,00 very high validity category, display advisability with value of Vc=1,00 very high validity category, and graphical advisability with value of Vc=1,00 very high validity category, it was suitable to be used as a learning material.Â Keywords: Student Worksheet, POE, Development Research, Validity.